Editome landscape of CCM-derived endothelial cells. Issue 1 (31st December 2022) - Scimone, Concetta; Alibrandi, Simona; Donato, Luigi; Alafaci, Concetta; Germanò, Antonino; Vinci, Sergio L.; D'Angelo, Rosalia; Sidoti, Antonina
ABSTRACT: By regulating several phases of gene expression, RNA editing modifications contribute to maintaining physiological RNA expression levels. RNA editing dysregulation can affect RNA molecule half-life, coding/noncoding RNA interaction, alternative splicing, and circular RNA biogenesis. Impaired RNA editing has been observed in several pathological conditions, including cancer and Alzheimer's disease. No data has been published yet on the editome profile of endothelial cells (ECs) isolated from human cerebral cavernous malformation (CCM) lesions. Here, we describe a landscape of editome modifications in sporadic CCM-derived ECs (CCM-ECs) by comparing editing events with those observed in human brain microvascular endothelial cells (HBMECs). With a whole transcriptome-based variant calling pipeline, we identified differential edited genes in CCM-ECs that were enriched in pathways related to angiogenesis, apoptosis and cell survival, inflammation and, in particular, to thrombin signalling mediated by protease-activated receptors and non-canonical Wnt signalling. These pathways, not yet associated to CCM development, could be a novel field for further investigations on CCM molecular mechanisms. Moreover, enrichment analysis of differentially edited miRNAs suggested additional small noncoding transcripts to consider for development of targeted therapies.